Identification of KasA as the cellular target of an anti-tubercular scaffold - Katherine A. Abrahams (Nature Portfolio, 2016)
Screens for bactericidal compounds have resulted in promising anti-tubercular hits. Here, the authors analyse in detail the target of an indazole sulfonamide (GSK3011724A), and find that it has a different mode of inhibition compared to other Kas inhibitors of fatty acid biosynthesis in bacteria.